The use of satellite remote sensing for the management of cultural heritage sites in Cyprus - Hadjimitsis, Diofantos G.; Themistocleous, Kyriacos; Ioannides, Marinos (My University, 2005)
Earth observation from space has given us a new perspective of our planet and has become an essential technique for the understanding and monitoring of changes at various scales from local to regional and global. Numerous applications have been developed, in particular for land management, such as agriculture, forestry, land use and land cover and the management of cultural and natural heritage areas. The satellite images provide the only possibility for the mapping of the heritage areas because of their instant availability and high resolution. This paper presents the preliminary results obtained from the application of satellite remote sensing techniques to monitor cultural heritage areas in Cyprus using high resolution satellite imagery. Indeed, an IKONOS pan-sharpened 1m resolution and Quickbird 0.62m resolution satellite images acquired in 2000 and 2003 respectively have been used for the Paphos District area to identify, survey and investigate possible land-cover changes near the cultural heritage areas. The resulting database is an essential tool for decision-making in heritage management. Methodology to locate, monitor and map cultural heritage sites is suggested in this paper.
Keywords: Archaeology; Cartography; GIS; Land Cover; Monitoring; Database; IKONOS; Quickbird